Modeling Hepatitis C Transmission to Inform Public Health Strategies and Long-Term Control - Jothi, Naresh Kumar; M, Jayaprakash; D, Sukumaran.; V, Vadivelu; Mattuvarkuzhali, C. (Trends in Immunotherapy, 2025)
The majority of people today would suffer and pass away from the hepatitis C virus (HCV); there is little knowledge of the illness in the world. Although many individuals have HCV characteristics and are affected, several individuals do not genuinely believe that this is a major issue. They are simply visiting the hospital to get short-term relief from symptoms like fatigue, nausea, jaundice; in long-term situations, they may experience fluid accumulation in the belly and easily bruise. Later on, it will develop into a chronic illness that causes liver cancer, liver failure, and scarring of the liver (cirrhosis). Since HCV continues to be a major cause of death among the populations, we established a compartmental framework for the nationwide outbreak in the current research, classifying those infected into two sections with the most effective control. To get the fundamental reproduction number, first, we employed the Next-Generation Matrix method to identify the model’s endemic and disease-free equilibrium point. Using infected and disease-free equilibrium points with reproduction number coordination, as well as MATLAB software to simulate the model’s numerical equations, the local and global stability were analysed.